2001
DOI: 10.1097/00006454-200106000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of documented viral respiratory infections and acute otitis media in a cohort of children followed from two to twenty-four months of age

Abstract: The seasonal coincidence of URI and AOM demonstrated the obvious role of URI in the pathogenesis of AOM. The occurrence of rhinoviruses and RS virus in URI was strikingly more common than that of any other virus tested. Although rhinoviruses were definitely the most frequently found viruses in NPA specimens, the association of RS virus with concurrent AOM was relatively higher than that of any other virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
123
1
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(146 citation statements)
references
References 33 publications
12
123
1
9
Order By: Relevance
“…Assays that screen for HRV typically target the highly con- served 5Ј UTR for amplification (5,9,10,27,38). However, in addition to detection, identification of the infecting species or serotype is of key importance diagnostically for the detection of mixed infections or a reinfection with different HRV serotypes, as well as in broader clinical investigations of the relationship between a serotype or species with disease severity and in epidemiological investigations of the circulation and turnover of HRVs (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assays that screen for HRV typically target the highly con- served 5Ј UTR for amplification (5,9,10,27,38). However, in addition to detection, identification of the infecting species or serotype is of key importance diagnostically for the detection of mixed infections or a reinfection with different HRV serotypes, as well as in broader clinical investigations of the relationship between a serotype or species with disease severity and in epidemiological investigations of the circulation and turnover of HRVs (20).…”
Section: Discussionmentioning
confidence: 99%
“…HRV infections are transmitted most commonly by the respiratory-salivary route, both by person-to-person contact and by airborne transmission. In temperate countries, infections occur primarily in two peaks, with the first being in April and May and the second being in September and October (24,38). HRV infections occur in all age groups during all seasons, with a 90% past infection frequency by the age of 2 years (2).…”
mentioning
confidence: 99%
“…In developed countries, infants experience several RTIs during the first year of life and one quarter suffer from recurrent or prolonged infections (1,2). RTIs often coincide with or precede acute otitis media (AOM), the most common cause for antibiotic use in children (3).…”
mentioning
confidence: 99%
“…This event was the genesis of investigations into the epidemiology and pathology of viral-bacterial infections revealing other associations between pathogens that cause infections of the upper and lower respiratory tract. Since that time, studies with humans have shown that respiratory viruses can enhance bacterial colonization of the nasopharynx (4,13,44,49) and facilitate bacterial invasion and spread to the middle ear (21,48), the sinuses (12,17), and the lungs (25,28). This association is most evident for influenza virus because of the striking impact on mortality from secondary bacterial pneumonia (43).…”
mentioning
confidence: 99%